Derivation of two induced pluripotent stem cell lines from a healthy control subject - Zhang, Dan; Huang, Di; Larcher, Leon M.; Zaw, Khine; Chen, Shang-Chih; Jennings, Luke; Lamey, Tina M.; Thompson, Jennifer A.; McLaren, Terri L.; Chen, Fred K.; McLenachan, Samuel (Stem cell research, 2025)
Two human induced pluripotent stem cell lines, LEIi021-A and LEIi021-B, were derived from dermal fibroblasts from a healthy control subject from an Australian Aboriginal family with retinitis pigmentosa-11. Reprogramming was performed using episomal vectors expressing OCT4, SOX2, LIN28, L-MYC, KLF4 and mp53DD. Pluripotency markers were expressed in both LEIi021-A and LEIi021-B lines. The two cell lines displayed normal karyotypes and demonstrated the ability to differentiate into embryoid bodies with the three primary germ layers and retinal pigment epithelial cells.